Legal Analysis of Related Party Transactions in the BRICS Countries - К. Brahma (BRICS Law Journal, 2024)
Legal literature in the past has often debated whether concentrated corporate ownership (i.e. sizeable corporate conglomerates and corporate enterprises owned by business families or the government of a State) in a relatively close market leads to a high volume of related party transactions between the corporations in the respective market. The emerging economies attract substantial foreign investment due to the rapid growth of their markets and the presence of large publicly listed companies. Concentrated ownership structures in these countries tend to result in the expropriation of resources by controlling shareholders for their personal enrichment. There has been a high corporate failure rate due to related party transactions, despite the adoption of regulatory reforms that promote transparency, accountability, and fairness. Listed companies in the BRICS countries are marked by concentrated ownership structures controlled by either a family or the State. Although there are differences in ownership structures as well as indications of agency problems in the United States and the United Kingdom, the BRICS countries have adopted the same legal strategies to prevent unfair or abusive related party transactions in their respective countries, such as the appointment of independent directors, independent audit committees, CEO duality, and disclosure requirements. This study seeks to conduct cross-country comparative research to assess the ways in which the BRICS countries have regulated related party transactions. Each of the BRICS countries has adopted different monitoring mechanisms to prevent abusive related party transactions, which will be examined in the course of this research.